Does Exposure To Household and Ambient Air Pollution Pose a Risk To Cardiovascular Health? - A Cross-Sectional Study in Nepal. - Om P Kurmi,; S Smith, W Cairns; Devereux, Graham S; Sadhra, Steven; Semple, Sean; Steiner, Markus F C; Lam, Kin-Bong Hubert; Padam Simkhada,; Jon G Ayres, (Universiti Kebangsaan Malaysia, 2013)
Over half the world’s population is exposed daily to very high levels of household air pollutants arising from burning biomass fuels; however the effects of these pollutants on cardiovascular health have not been fully established. This study aimed to compare the relationship between household indoor and outdoor air pollution with cardiovascular health in biomass and non-biomass exposed group.